Hermeneutics of Memory for Tourist Promotion: An Upcycling Process of Spanish Civil War Air Raid Shelters - Rosser Limiñana, Pablo; Soler Ortiz, Seila (Global Journal of Tourism, Leisure and Hospitality Management, 2024)
This study delves into the transformative role of air-raid shelters from the Spanish Civil War in Alicante, Spain, highlighting their significance in the recovery and preservation of intangible heritage. Through a detailed hermeneutic analysis based on interviews and existing research, the investigation explores the shelters' contribution to cultural identity, memory, and sustainable urban development. It reveals how the hermeneutics of memory, applied via a rigorous scientific approach, serves as a vital tool for justifying, rehabilitating, and planning these historical sites for tourism aligning with the Sustainable Development Goals. The rehabilitation of these shelters not only acts as a conservation effort but also as a means to promote cultural tourism enhancing Alicante's cultural and tourist offerings. The study underscores the shelters' dual role as educational resources and tourist attractions, facilitating a deeper understanding and connection with the past, and fostering community development and sustainability.
Keywords: sir raid shelters; hermeneutics of memory; sustainable urban development; cultural tourism; spanish civil war